Pancreatic Cancer Diagnostics and Treatment--Current State - Krška, Zdeněk; Šváb, Jan; Hoskovec, David; Ulrych, Jan (Prague medical report, 2015)
Pancreatic ductal adenocarcinoma (PDAC) represents permanent and ever rising issue worldwide. Five-year survival does not exceed 3 to 6%, i.e. the worst result among solid tumours. The article evaluates the current state of PDAC diagnostics and treatment specifying also development and trends. Percentage of non-resectable tumours due to locally advanced or metastatic condition varies 60-80%, mostly over 80%. Survival with non-resectable PDAC is 4 to 8 months (median 3.5). In contrast R0 resection shows the survival 18-27 months. Laboratory and imaging screening methods are not indicated on large scale. Risk factors are smoking, alcohol abuse, chronic pancreatitis, diabetes mellitus. Genetic background in most PDAC has not been detected yet. Some genes connected with high risk of PDAC (e.g. BRCA2, PALB2) have been identified as significant and highly penetrative, but link between PDAC and these genes can be seen only in 10-20%. This article surveys perspective oncogenes, tumour suppressor genes, microRNA. Albeit CT is still favoured over other imaging methods, involvement of NMR rises. Surgery prefers the "vessel first" approach, which proves to be justified especially in R0 resection. According to EBM immunotherapy same as radiotherapy are not significant in PDAC treatment. Chemotherapy shows limited importance in conversion treatment of locally advanced or borderline tumours or in case of metastatic spread. Unified procedures cannot be defined due to inhomogenous arrays. Surgical resection is the only chance for curative treatment of PDAC and depends mainly on timely indication for surgery and quality of multidisciplinary team in a high-volume centre.
Keywords: Chemotherapy; nádory slinivky břišní; Pancreatic cancer; Genetic predisposition; Humans; Biomarkers; Whipple resection; Pancreatic Neoplasms; duktální karcinom slinivky břišní; lidé; Carcinoma, Pancreatic Ductal